Diabetes Mellitus in a Patient With Lafora Disease: Possible Links With Pancreatic β-Cell Dysfunction and Insulin Resistance - Nicolescu, Ramona C.; Al-Khawaga, Sara; Minassian, Berge A.; Hussain, Khalid (Frontiers in Pediatrics, 2019)
Lafora disease (LD) is a rare autosomal recessive disorder characterized by progressive myoclonic epilepsy followed by continuous neurological decline, culminating in death within 10 years. LD leads to accumulation of insoluble, abnormal, glycogen–like structures called Lafora bodies (LB). It is caused by mutations in the gene encoding glycogen phosphatase (EPM2A) or the E3 ubiquitin ligase malin (EPM2B/NHLRC1). These two proteins are involved in an intricate, however, incompletely elucidated pathway governing glycogen metabolism. Formation of EPM2A and malin signaling complex promotes ubiquitination of proteins participating in glycogen metabolism, and dysfunctional mutation leads to formation of LB. Herein, we describe a 13 year-old child with LD due to a NHLRC1 (c.386C>A, p.Pro129His) mutation, who has developed diabetes mellitus and was treated with metformin. We discuss how basic mechanisms of LD could be linked to insulin resistance and the associated diabetes.